The Effectiveness of Marriage Age Limit Regulations - Chamidah, Chamidah; Khisni, Akhmad (Law Development Journal, 2021)
This research aims to know the effectiveness of the regulation on the marriage age limit based on Act No. 16 of 2019. The research method used is the juridical-sociological research method, The juridical approach will discuss research using laws relating to the regulation of the marriage age limit and marriage dispensation contained in Act No. 1 of 1974, Constitution Number 16 of 2019, the Compilation of Islamic Law, and others, while a sociological approach is used to find out and analyze the judge's view of the case for a marriage dispensation application. The results of the study concluded that the regulation of the minimum age limit for women to marry was raised in Act No. 16 of 2019 was not effective for the people of Jepara Regency, the increase in applications for marriage dispensation at the Jepara Religious Court experienced a very significant increase, as indicated by the number of applications for marriage dispensation experienced a very significant increase, 2 times more than before the birth of Act No. 16 of 2019.